Free cooling potential of air economizer in residential houses in Canada. (January 2020) - Li, Bo; Wild, Peter; Rowe, Andrew
Abstract: An air-side economizer uses outside air to reduce building cooling system energy demand. In Canada, air economizers are widely applied in non-residential building cooling systems but are rarely implemented in residential single-family houses. This study investigates the free cooling potential of the outside air through a temperature controlled air-side economizer in a hypothetical single-family house for sixteen cities across Canada. A series of thermal models with different aspect and window-to-wall ratios are developed to simulate the hourly and annual building cooling demand for each simulation case. The impacts of climatic conditions and building geometry on the potential annual usable and maximum available free sensible cooling are investigated. Results show that the available free cooling potential ranges from 50% up to 325% of the building cooling needs due to the mild summer weather in most areas of Canada; however, a majority of available free cooling is not able to be utilized. Further studies focused on finding the solutions to maximize the outside air free cooling usage to minimize the building HVAC system cooling energy use is necessary. Highlights: It is most effective to employ the air-side economizer in the mild summer weather conditions. Houses with high cooling demand benefit more by using an air-side economizer than those with low cooling demand. Cooling demand can be completely met by free cooling at times when the outdoor air temperature is higher than 13 °C. Thermal storage may offer a way to increase usable free cooling being limited by the building instantaneous cooling.